MY SAY: CSR - corruptible social responsibility? - Abd Razak, Dzulkifli (2009)
Queen Elizabeth II has decided to omit leading figures associated with the financial world from her New Year's honours list in view of their alleged role in the current economic crisis. The palace says: "When millions of families are struggling to keep their homes and many people live in fear of losing their jobs, it would be unjust to dole out honours to rich bankers." The honours system must reflect the moods of the times as well as public opinion, it adds. And so, the Queen may not be amused to find out who gets what at one Annual Corporate Report Awards held here recently. This event might not have been as prestigious, but millions of Malaysian families are also struggling like their British counterparts.